3D food printing: a categorised review of inks and their development. Issue 3 (3rd July 2019) - Voon, Siew Li; An, Jia; Wong, Gladys; Zhang, Yi; Chua, Chee Kai
ABSTRACT: 3D food printing, or the use of food materials in additive manufacturing, has been a topic of interest to the commercial sector for the past decade. Recently, there has also been increased attention from the academic field, with a considerable volume of research being published. Most of these studies have focused on developing food inks for extrusion-based printing beyond conventional materials such as chocolate, resulting in a much wider range of printable and edible materials. The formulations of these materials are of particular interest, as they determine the rheological and mechanical properties of food inks, thereby affecting the final quality of the printed food. This article reviews the current status and possible directions in food ink research across five categories, namely confectionery, dairy, hydrogels, plants, and meat. The roles of additives in these inks are then discussed, followed by the remaining challenges and potential opportunities in 3D food printing.